Effects of Virtual Reality Integration on Student Engagement in Online Learning in Nigeria - Chinedu, Ayodele (American Journal of Online and Distance Learning, 2024)
Purpose: The aim of the study was to assess the effects of virtual reality integration on student engagement in online learning in Nigeria. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Utilizing VR technology in online learning environments has shown to significantly enhance student engagement through immersive and interactive experiences. Study indicate that students exhibit higher levels of motivation, interest, and participation when learning through VR compared to traditional online methods. The immersive nature of VR fosters a sense of presence and involvement, leading to increased attention and focus during learning activities. Moreover, VR facilitates experiential learning, allowing students to explore complex concepts in a simulated environment, which enhances comprehension and retention. Additionally, VR-based activities promote collaboration and social interaction among students, contributing to a sense of community in online learning environments. Overall, integrating VR into online learning holds great potential for improving student engagement and learning outcomes in diverse educational settings. Implications to Theory, Practice and Policy: Self-determination theory, cognitive load theory and social learning theory may be used to anchor future studies on assessing the effects of virtual reality integration on student engagement in online learning in Nigeria. Provide professional development opportunities and training programs for educators to enhance their competence in integrating VR technology into online courses effectively. Advocate for increased funding and resources to support the adoption and implementation of VR technology in educational settings.